Use of interval hypoxi-hyperoxic training in aesthetic medicine - Z. Z. Kardashova; I. A. Vasilenko; G. I. Grigoryev (Лечащий Врач)
The article presents analysis of the effectiveness of using interval hypoxi-hyperoxic training (IHHT) technology in aesthetic cosmetology. It is shown that the hypoxi-hyperoxic therapy improves parameters of gas exchange and hemodynamics in patients at systemic level. In the face and neck area, the condition of capillary network is improved, the microcirculation and the local blood concentration are increased. The obtained results allow to recommend IHHT technology for activating of complex rejuvenation of aged patients’ organism and correction of adverse changes in the skin of the face and neck.